PEMBINAAN PEMANFAATAN PEKARANGAN UNTUK KOMODITI HORTIKULTURA DI DESA GOHA KECAMATAN BATU MANDI KABUPATEN BALANGAN - Suparno Suparno; Ruben Tinting S; Ellen Christ Tambunan (Bajang Institute, 2022)
As an effort to improve the knowledge and skills of rural farmers, service activities have been carried out with the topic